Anti-public administration in India - Ray, Jayanta Kumar (1994)
"In this critical write up on present administrative scenario, the author brings to the fore several persistent negative traits of Indian administrative system to justify the title of the article. He also illustrates his point with reflections on recent happenings in India-Pakistan and India-China relations"
Keywords: Public administration - India; Public administration